Feasibility of an external call center in Singapore. - Tan, Esther Siok Yee. (2008)
The success of call centers overseas has motivated us to research on the feasibility of external call centers in Singapore. We have done a thorough research in three main aspects: techonological, economic, and behavioural to come up with our conclusion.